A core–periphery framework in stock markets of the euro zone - Dias, J. G.; Ramos, S. B. (Economic Modelling, 2013)
The introduction of the euro was expected to have an effect not only on real convergence of economies but also on stock markets. This research compares the dynamics and synchronization of stock market regimes in European markets before and after the euro launch. Countries of the euro zone are found to have different dynamics with regard to switching between bull and bear markets, but the differences become less pronounced after the introduction of the single currency, increasing the overall level of stock market synchronization. Nevertheless, Austria and Portugal reduced the level of regime synchronization with other stock markets. The results delineate a framework of core-periphery stock markets, i.e., a large group of stock markets that share the same market regime, with some others on the periphery characterized by distinctive behavior.